Liderzy i partie IV Rzeczypospolitej na łamach wybranych dzienników opinii w 2005 roku. Analiza badań - Kuca, Paweł (Polityka i Społeczeństwo, 2020)
The main purpose of the article is to present the unique authors researches related to press studies, which concern political leaders and the political groups involved in the so-called project of construction of the IV Republic. Researches covered the period after the parliamentary and presidential elections in 2005. The press analysis include the “Gazeta Wyborcza” and “Republic”, two all-Polish quality newspapers with the highest sales in this section of the press in 2005. The main purpose of this research is an analysis of the attitudes of chosen titles to politicians and political groups which co-create the authority camp of IV Republic of Poland, from the beginning and during the initial activity in 2005. For examinations the method of content analysis was applied.